Cerebro‐oculo‐facio‐skeletal syndrome caused by the homozygous pathogenic variant Gly47Arg in ERCC2. Issue 3 (27th December 2020) - Reunert, Janine; van den Heuvel, Alijda; Rust, Stephan; Marquardt, Thorsten
Abstract: DNA damage repair is a pivotal mechanism in life. The nucleotide excision repair pathway protects the cells against DNA damage and involves XPD, an ATP dependent helicase that is part of the multisubunit protein complex TFIIH. XPD is encoded by the excision repair cross‐complementation group 2 gene ( ERCC2 ). Only three patients with cerebro‐oculo‐facio‐skeletal syndrome (COFS), caused by mutations in ERCC2, have been published so far. This report describes a boy with the homozygous amino acid change p.Gly47Arg in XPD. He presented with profound microcephaly, psychomotor retardation, failure to thrive, cutaneous photosensitivity, a bilateral hearing deficit and optic atrophy, thrombocytopenia, and recurrent episodes of pneumonia. We report the first homozygous occurrence of the pathogenic variant Gly47Arg in the ERCC2 gene. Occurring homozygous, this variant was associated with COFS syndrome, leading to early death of the patient at the age of 21 months.